2018
DOI: 10.1017/rep.2017.38
|View full text |Cite
|
Sign up to set email alerts
|

Between Anger and Engagement: Donald Trump and Black America

Abstract: History suggests that social movements for change are often met with powerful counter-movements. Relying upon movement counter-movement dynamics, this paper examines whether or not contemporary reactionary conservatism—in this case Donald Trump's candidacy in 2016, offers an opportunity for African-American mobilization. Today, the reactionary right presents a threat to racial progress and the black community as it has grown from direct opposition to the election of President Obama, immigration reform, and gay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…In addition, President Trump’s taste for controversy, aggrandizement, and bold pronouncements of law and order while using explicit racist, sexist, and Islamophobic language raises serious threats to already vulnerable communities; recent research directly connects opposition to Trump, which is characterized by perceptions of racism, to significantly higher levels of political interest and engagement (Towler and Parker 2018). Thus, although BLM’s use of online organizing may be limiting the power of the movement to urge blacks to act—research suggests face-to-face contact is the strongest mobilizer (Gerber and Green 2000)—we believe that the organizational network, specifically its built-in-leaders, such as Kaepernick, represent a mobilizing elite.…”
Section: The Case For Colin Kaepernickmentioning
confidence: 99%
“…In addition, President Trump’s taste for controversy, aggrandizement, and bold pronouncements of law and order while using explicit racist, sexist, and Islamophobic language raises serious threats to already vulnerable communities; recent research directly connects opposition to Trump, which is characterized by perceptions of racism, to significantly higher levels of political interest and engagement (Towler and Parker 2018). Thus, although BLM’s use of online organizing may be limiting the power of the movement to urge blacks to act—research suggests face-to-face contact is the strongest mobilizer (Gerber and Green 2000)—we believe that the organizational network, specifically its built-in-leaders, such as Kaepernick, represent a mobilizing elite.…”
Section: The Case For Colin Kaepernickmentioning
confidence: 99%
“…Scholars have also focused on the relevance of group identity and group consciousness for elevating minority political participation (Miller et al 1981). Other researchers documents how political threat mobilizes minority populations (Pantoja and Segura 2003; Towler and Parker 2018).…”
Section: Political Engagementmentioning
confidence: 99%
“…Among various racialized groups, scholars found a positive correlation between anger and a willingness to vote among Black Americans (Banks 2014;Towler and Parker 2018) and Latinx Americans (Gutierrez et al 2019). However, Phoenix (2019) and Valentino et al (2011) found that anger is not politically mobilizing in the absence of skills and resources.…”
Section: Emotion In Collective-action Appealsmentioning
confidence: 99%